(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
In the article the epithet as creative tool of landscape and portrait descriptions is analyzed in Borys Grinchenko’s prose. It is emphasized on role of epithet in representation of characters’ appearance (their age, body, face, voice, clothes). The epithets that accompany with somatisms (face, head, hair, forehead, eyebrows, eyes, lips, beard) and that characterize their size, shape, color, express state, mood and personality of person, his intellect and feelings are represented. The epithets are divided into ways of designation of relevant indication by the semantic settings, language level, quantitative composition and solidity of connection with the signified word. Also it is clarified that portraitisation predominates in author’s prose work.